Perilaku Abnormal Tokoh pada Novel Kelab dalam Swalayan Karya Abi Ardianda - Saputra, Rizal Abriyan Syah; Dasuki, Mohammad Ramdon (Ruang Kata, 2024)
This study aims to describe the form of abnormal behavior in the characters in the novel Kelab dalam Swalayan by Abi Adrianda. This study uses a literary psychology approach with the theory of psychopathology or abnormal psychology from Gerald C. Davison. The method used in this study is a qualitative description in which the data will be grouped according to the formulation of the problem and then described systematically so that it is easy for readers to understand. The data in this study are quotes or dialogues that come from data sources, namely the novel entitled Kelab dalam Swalayan by Abi Ardianda. The stages of making this research begin with reading data sources, studying and reviewing data sources, and analyzing data according to the help of psychopathology theory. The results of this study obtained characters who have abnormal behavior, including: Sonja, Ibu, and Kamala. The form of abnormal behavior is divided into two major forms, namely psychological disorders and age range disorders, then grouped into sub-units of each form of abnormal behavior